Mussel-inspired polydopamine decorated alginate dialdehyde-gelatin 3D printed scaffolds for bone tissue engineering application - Ghorbani, Farnaz; Minjoo, Kim; Monavari, Mahshid; Ghalandari, Behafarid; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2022)
This study utilized extrusion-based 3D printing technology to fabricate calcium-cross-linked alginate dialdehyde-gelatin scaffolds for bone regeneration. The surface of polymeric constructs was modified with mussel-derived polydopamine (PDA) in order to induce biomineralization, increase hydrophilicity, and enhance cell interactions. Microscopic observations revealed that the PDA layer homogeneously coated the surface and did not appear to induce any distinct change in the microstructure of the scaffolds. The PDA-functionalized scaffolds were more mechanically stable (compression strength of 0.69 & PLUSMN; 0.02 MPa) and hydrophilic (contact angle of 26) than non-modified scaffolds. PDA-decorated ADA-GEL scaffolds demonstrated greater durability. As result of the 18-days immersion in simulated body fluid solution, the PDA-coated scaffolds showed satisfactory biomineralization. Based on theoretical energy analysis, it was shown that the scaffolds coated with PDA interact spontaneously with osteocalcin and osteomodulin (binding energy values of -35.95 kJ mol(-1) and -46.39 kJ mol(-1), respectively), resulting in the formation of a protein layer on the surface, suggesting applications in bone repair. PDA-coated ADA-GEL scaffolds are capable of supporting osteosarcoma MG-63 cell adhesion, viability (140.18% after 7 days), and proliferation. In addition to increased alkaline phosphatase secretion, osteoimage intensity also increased, indicating that the scaffolds could potentially induce bone regeneration. As a consequence, the present results confirm that 3D printed PDA-coated scaffolds constitute an intriguing novel approach for bone tissue engineering.
CRIS-Team WoS Importer:2022-09-02